2021
DOI: 10.21037/jtd-20-2360
|View full text |Cite
|
Sign up to set email alerts
|

Global burden of medication non-adherence in chronic obstructive pulmonary disease (COPD) and asthma: a narrative review of the clinical and economic case for smart inhalers

Abstract: Medication non-adherence to asthma and chronic obstructive pulmonary disease therapy poses a significant burden for patients and societies. Non-adherence encompasses poor initiation, implementation (including poor inhalation technique) and non-persistence. Globally, non-adherence is associated with poor clinical outcomes, reduced quality of life and high healthcare and societal costs. Costs are mainly caused by excess hospitalizations and impaired work productivity. Multiple intervention programs to increase a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 100 publications
0
27
0
Order By: Relevance
“…Several simple methods can be applied to address this problem: using simplified medication regimens, increasing the patient’s knowledge of self-management, and improving the skills of health care workers in patient education and adherence counseling 36 . Smart inhalers have already been created, which are not yet used in practice, but have already yielded good results regarding monitoring and managing medication adherence, however, more research is needed 37 . It is important to note that there is a large shortage of primary health care workers, especially in more remote Kyrgyz regions, and due to the heavy workload of physicians, they physically do not have time or forget to evaluate or support patients’ adherence.…”
Section: Discussionmentioning
confidence: 99%
“…Several simple methods can be applied to address this problem: using simplified medication regimens, increasing the patient’s knowledge of self-management, and improving the skills of health care workers in patient education and adherence counseling 36 . Smart inhalers have already been created, which are not yet used in practice, but have already yielded good results regarding monitoring and managing medication adherence, however, more research is needed 37 . It is important to note that there is a large shortage of primary health care workers, especially in more remote Kyrgyz regions, and due to the heavy workload of physicians, they physically do not have time or forget to evaluate or support patients’ adherence.…”
Section: Discussionmentioning
confidence: 99%
“…This can be measured using self-reported patient diaries, which are prone to reporting bias, or more accurately using electronic inhaler monitors. 13 Studies with these electronic devices show that persistence with treatment is relatively poor, but this may be improved by educational interventions. A recent UK study showed that average persistence for children with asthma was 49% for those who were monitored but received no reminders, and 70% for those who received reminders to take their treatment.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…Unfortunately, approximately 22–78% of patients with asthma and COPD and 31–53% of CF patients are poorly adherent to their inhaled medications [ 36 , 37 ]. Errors in inhalation techniques occur in a percentage of 6.8–43.2%, and only 10–52% of physicians are adequately informed regarding proper device use [ 38 , 39 ].…”
Section: Limitations Of Currently Available Dpismentioning
confidence: 99%
“…Doser TM (Meditrack Inc., Hudson, MA, USA), Smart Mist Âź (Aradigm Corporation, Hayward, CA, USA), MDILog TM (Westmed Technologies Inc., Englewood, USA), Smart Inhaler Tracker (Adherium Ltd., Auckland, New Zealand), and Smart Track TM (Adherium Ltd., Auckland, New Zealand) were some of the first digitalized pMDIs [ 36 , 107 ]. Except for the Doser, all of them provide records regarding date and time of actuation, as well as specific reminders through ringtones [ 107 ].…”
Section: Digitalization: From Nebulizers and Pmdis To Dpismentioning
confidence: 99%
See 1 more Smart Citation